PENYEBARAN KUALITAS BATUBARA BERDASARKAN KODIFIKASI SECARA REGRESI GANDA DAN ANALISIS KLASTER (STUDI KASUS BATUBARA BANIARSARI, SUMATERA SELATAN) - Titisariwati, Indun
The proximate and ultimate analysis of coal exploration data can be used to evaluate the coal quality of a certain area. Currently the-coal quality grouping uses manual method, but in this study will be used statistical method. In this methods, the multiple regression and cluster analysis methods will be used for grouping the investigated areas based on several coal quality parameters. The qualitative parameters GCV, TM, VM, TS and Ash were first searched using the multiple regression method and then determined the number of classes of each parameter as well as the interval length of each class formed the permutation. With the FORTRAN program codification of each drill holes will be conducted. Beside the multiple regression with the cluster analysis, codification of each drill holes will be conducted by using Qmode. The results of the two methods a similar, based on the average value of each qualitative parameters of every groups from the map distribution of coal quality. However for simplicity grouping, it is advisable to use cluster analysis. From this study results it can be concluded that the both methods are capable for grouping areas of which can be used to determine the trend of distribution of coal quality.